Is time an extra dimension in 3D cell culture? - Asthana, Amish; Kisaalita, William S. (Drug discovery today, 2016)
Time or the temporal microenvironment is a parameter that is often overlooked in 3D cell culture. However, given that the 3D system is a dynamic entity, there exists bidirectional signaling between the cells and their microenvironment and, in time, cells can develop the capacity to modulate their environment. We make this case here by illustrating the relation between the temporal dimension and other microenvironmental parameters and demonstrate how the exogenously incorporated microenvironmental factors (MEFs) can be rendered less significant with time. Such knowledge can guide construct design to make 3D platforms architecturally simpler by eliminating redundancy. We further show that there is a need to establish the point at which the construct is complex enough such that its use yields responses that more closely emulate in vivo outcomes.